The Role of Family Counseling in Overcoming Juvenile Delinquency - Fauzi Isra; Neviyarni Neviyarni; Yarmis Syukur (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2021)
Juvenile delinquency is one of the deviant behaviors that requires special attention and good understanding and proper handling of the resolution process because it is an important factor for the success of adolescents in the next life, considering that the teenage transition period is the most decisive period. There are several roles that parents can do in overcoming juvenile delinquency, including the process of fostering and guidance carried out by the family. Parents try to create a harmonious, communicative and comfortable family for adolescents and help adolescents in their social and adjustment processes. Family counseling is a training process that is focused on the client's parents as the most influential person in determining the system in the family. This is done not to change the personality or character of the family members involved but to change the family through changing the behavior of the parents. If the behavior of the parents changes, it will affect the members in the family.